Tobacco use among 11-16 years old students of Sousse Tunisia in 2020: a cross sectional study with the GYTS method - Rania Bannour; Sana Bhiri; Asma B. Cheikh; Hela Ghali; Salwa Khefacha; Mohamed B. Rejeb; Houyem S. Latiri (Population Medicine)
Introduction Despite tobacco control prevention programs, many adolescents start smoking at school age. The main objectives of this study were to assess the prevalence of smoking, secondhand smoke exposure, and susceptibility to smoking among middle-school students aged 11–16 years, using the Global Youth Tobacco Survey (GYTS), in Sousse, Tunisia, 2020.